Analysis of three-phase coupled dust reduction law of external spray in synthesized digging face - Haiming YU; Peibei WANG; Yuxi YE; Weimin CHENG (Meitan kexue jishu)
Due to the gradual realization of mechanization and intelligence in mine excavation technology, the problem of dust pollution in the comprehensive excavation face has become increasingly serious. In order to study the dust fall law of the spray system outside the excavation face under different arrangement methods, based on the three-phase coupling method of gas phase (air flow) – solid phase (dust) – liquid phase (droplets), the diffusion law of droplets and dust under different nozzle arrangement schemes was simulated and analyzed. The simulation results show that, without changing the spray pressure, as the number of nozzles increases, the air flow around the cutting head is intensified by the influence of droplets, but the overall air flow field structure of the roadway is less affected by droplets. On the compressed air side of the roadway, fog droplets accumulate in the roof area of the roadway. On the exhaust side, due to the collision effect of axial and radial air flows, the fog droplets are concentrated between the cutting face area of the tunneling working face and the exhaust outlet, and the droplet size significantly decreases in the air curtain area. The distribution of dust mass concentration on the roadway cutting surface is greatly influenced by the nozzle layout scheme. With the increase in the number of sprays, the dust accumulation phenomenon in the top and compressed air side areas of the roadway cutting surface gradually weakens, and the control effect of droplets on dust gradually strengthens. When the dust mass concentration at the height of the roadway airway is between 6 and 8 nozzles, the dust pollution situation is effectively controlled. When the nozzle layout scheme is less than 6 nozzles, the coverage effect of droplets on the cutting surface is insufficient, the dust control effect is poor, and the mass concentration of droplets at the height of the airway is small. When the nozzle layout scheme reaches 6 nozzles, the control effect of dust pollution at the height of the airway in the roadway is insufficient. When the nozzle arrangement scheme is 7 nozzles, the overall droplet coverage effect of the roadway is the best. The maximum dust mass concentration in the suction side area of the roadway cutting surface is 38.5 mg/m3. The dust mass concentration along the way is all lower than 20.0 mg/m3, and the dust mass concentration at the height of the airway is lower than 15.0 mg/m3. The fog droplets have the best overall coverage effect on the roadway, significantly reducing the dust pollution of the roadway and providing a theoretical basis for the optimal design of the external spray system in the comprehensive excavation face.